Peningkatan Taman Doa dengan Pendekatan Kolaboratif untuk Ruang Spiritual yang Inspiratif di Gereja Santo Leo Agung, Jakarta: Enhancement of A Prayer Garden through a Collaborative Approach for An Inspiring Spiritual Space at St. Leo Agung Church, Jakarta - Prabawasari, Veronika Widi; Furuhitho, X.; Susanto, Remigius Hari; Nugroho, Agus; Christina, Erma Triawati; Gunarto, Thomas Yuni (Vivabio: Jurnal Pengabdian Multidisiplin, 2025)
This Community Service (PkM) activity aims to address the needs of the congregation of St. Leo Agung Parish, East Jakarta, in enhancing and realizing a sacred and tranquil prayer garden as a means of devotion to Mary, Mother of the Redeemer. Stemming from the church's existing but unrealized master plan, this project faced the primary challenges of a limited land area of 67.20 m², coupled with the necessity to preserve existing trees. Through a collaborative approach, this PkM activity focused on two core areas: prayer garden planning and construction management. In the planning phase, the PkM team developed a prayer garden design embodying the concept of "Simplicity and Naturalness" within a spiritual space that reflects the humble character of Mary, the Praying Mother. This stage encompassed site identification, concept coordination, garden design creation, and the preparation of construction documents. In the construction management domain, the team provided comprehensive guidance, from selecting the implementing contractor and supervising quality and execution timelines, to finalizing construction and inaugurating the prayer garden, an event graced by the presence of the Archbishop of Jakarta, Mgr. Ignatius Suharyo. The outcome of this activity is the realization of the Our Lady of the Redeemer Prayer Garden, which has been inaugurated and blessed by the Archbishop of Jakarta, Mgr. Ignatius Suharyo. This prayer garden now serves as a spiritual space that enriches the faith of the congregation, reflects the simplicity and naturalness of the Virgin Mary, and demonstrates successful collaboration in creating an inspiring space. ABSTRAK Kegiatan Pengabdian kepada Masyarakat (PKM) ini bertujuan untuk merespon kebutuhan umat Paroki Santo Leo Agung, Jakarta Timur, dalam meningkatkan dan mewujudkan sebuah taman doa yang sakral dan menenangkan sebagai sarana devosi kepada Bunda Maria. Berangkat dari masterplan gereja yang telah ada namun belum terealisasi, proyek ini menghadapi tantangan utama berupa keterbatasan luas lahan 67.20 m², serta kebutuhan untuk memelihara pohon eksisting. Melalui pendekatan kolaboratif, kegiatan PkM ini berfokus pada dua bidang utama: perencanaan taman doa dan manajemen konstruksi. Dalam bidang perencanaan, tim PkM menghasilkan desain taman doa dengan konsep "Kesederhanaan dan Kealamian" pada ruang spiritual yang mencerminkan kesederhanaan sosok Bunda Sang Pendoa. Tahap ini melibatkan identifikasi lahan, koordinasi konsep, pembuatan desain taman, dan penyusunan dokumen konstruksi. Di bidang manajemen konstruksi, tim memberikan pendampingan mulai dari pemilihan kontraktor pelaksana, pengawasan kualitas dan waktu pelaksanaan, hingga finalisasi pembangunan dan peresmian taman doa yang dihadiri oleh Uskup Agung Jakarta, Mgr. Ignatius Suharyo. Hasil kegiatan ini adalah terbangunnya Taman Doa Maria Bunda Sang Penebus yang telah diresmikan dan diberkati oleh Uskup Agung Jakarta, Mgr. Ignatius Suharyo. Taman doa ini kini berfungsi sebagai ruang spiritual yang memperkaya iman umat, mencerminkan kesederhanaan dan kealamian Bunda Maria, serta menjadi bukti keberhasilan kolaborasi dalam mewujudkan ruang yang inspiratif.